Gestión de la atención pre-natal en la prevención y detección Temprana de anomalías congénitas por defectos del tubo Neural en recién nacidos. Estudio comparativo en el Hospital II ESSALUD y Hospital Minsa II-2 Tarapoto. 2014 - Piña Méndez, Jhoanna (2015)
This study entitled "Managing the Pre-Natal Care in the Prevention and Early Detection of Congenital Abnormalities neural tube defects in newborns. Comparative Study II Hospital essalud and MINSA II-2 Tarapoto Hospital. 2014 no experimental Quantitative, descriptive study of transversal, comparative, cut the interview survey And observation, where two checklists were developed and a test was used. The Population was 21 users, 23 professionals and 21 newborns. The results were: The incidence of newborns with congenital anomalies, II Hospital Essalud Tarapoto was 8 cases per 1000 live births and the MOH Hospital Tarapoto II-2 was 5 cases per 1000 live births. According diagnostic management of pre-natal Care, both institutions have management documents that standard prenatal care in Preventing birth defects. 70% of users were assisted by obstetrician and Gynecologist-obstetrician in both health facilities respectively. Their knowledge users For the prevention of congenital anomalies, is good (87.5%) in the Hospital essalud Tarapoto II Vs 61.5% of users MINSA Hospital Tarapoto II-2 that are located in the Level of Regular (61.5%) knowledge. The management of prenatal care in the prevention and early detection of congenital Anomalies, was only 10.6% in II Hospital essalud and 46.2% in the MOH Hospital II- 2 Tarapoto, the wide coverage gap 89.4% vs. 53.8% respectively. According Mechanisms of prenatal care to prevent birth defects MINSA II-2 Tarapoto Hospital, Does not inform or educate, and communicate its importance (0%), while the Hospital Essalud II reached 17.2%. According strategies for early uptake of the users to avoid The presence of congenital anomalies derived from a late entry into prenatal care, the Xiii MOH Hospital Tarapoto II-2 runs on a 100% action vs II Hospital essalud only 82.8%. In conclusion: The management of prenatal care in the prevention and detection of Congenital anomalies is more favorable in the MOH II-2 vs Tarapoto Hospital II Hospital essalud.